Impact of charging infrastructure on willingness to pay for EV: Mediating role of driving experience and behavior intentions - Ahmad, Sheraz; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2025)
Global primary transportation networks are affected by challenges associated with carbon emissions and rising oil prices. A growing population is opting for electric vehicles (EVs) because of their independent operation without reliance on gasoline and their lower pollution emissions. Establishing a charging infrastructure is necessary to stimulate consumer willingness to pay for EVs. Therefore, this study explored the impact of charging infrastructure on the willingness to pay, as well as the mediating role of driving experience and behavior intentions, using the theory of planned behavior. A quantitative methodology was employed, whereby data were gathered via a survey questionnaire distributed among Thai users residing in Bangkok, Thailand. Statistical analysis was conducted on data collected from 231 potential consumers using structural equation modeling and confirmatory factor analysis to validate the variables. This study revealed that charging infrastructure positively and significantly enhances the driving experience. The driving experience of an EV significantly affects behavior intentions, and positive behavior intentions significantly affect willingness to pay for an EV. Additionally, this study tested the sequential mediation of driving experience and behavior intentions, and the results revealed partial mediation. Furthermore, this study's findings indicate that the government and EV manufacturers should invest in developing charging infrastructure to enhance consumers' willingness to pay.
Keywords: Charging infrastructure; Driving experience; Electric vehicle; Theory of planned behavior; Willingness to pay